An oxo(corrolato)chromium(v) complex selectively kills cancer cells by inducing DNA damage. Issue 39 (19th April 2021) - Pradhan, Nitika; Garai, Antara; Patra, Bratati; Kar, Sanjib; Maiti, Prasanta K.
Abstract : A chromium(v )–oxo corrole complex induces cell death in cancer cell lines but has no effect in normal cells. It was also observed that the complex cleaves the DNA derived from cancer cell lines but not the DNA derived from normal cells. Abstract : An oxo(corrolato)chromium(v ) complex selectively kills leukemia cells. However, this complex did not induce cell death in primary non-cancer cells. It has been observed that oxo(corrolato)chromium(v ) complex induced cell death is associated with DNA damage. Interestingly, the DNA in primary cells largely remained unaffected. DNA isolated from normal and cancerous cell lines also follows similar trends. A chemical reductant, DTT, was used to probe the mechanism of DNA damage. However, it does not show any additive effect on DNA damage.